Scenario Planning on Increasing the Competitiveness of Food MSMEs in Jambi for The Next Five Years - Febriany Martiana Nasel; Pri Hermawan (Journal of International Conference Proceedings, 2021)
The target of the food MSME assistance program by the Indonesian FDA is to increase the competitiveness of food MSMEs through product licenses issued by the Indonesian FDA. However, many factors influence and have a significant impact on the ability of food MSMEs to meet registration requirements. The Indonesian FDA, especially in Jambi, needs to develop a strategy for assisting MSMEs in food to quickly adapt to changes in an uncertain future. The strategies are developed using a scenario planning approach. The key focal issue, driving forces, and key uncertainties are identified and analyzed using PESTEL and SWOT analyses, as well as data collection via literature reviews and expert interviews. According to the impact and uncertainty associated with the 13 driving forces, the primary sources of uncertainty regarding the competitiveness of food MSMEs in Jambi are the consistency of government policies and public awareness of food MSMEs' competitiveness. Combining these critical uncertainties results in a two-dimensional matrix containing four plausible scenarios: The Flash, The Dark Knight, Far From Home, and Infinity War. The province of Indonesian FDA in Jambi uses the implications, options, and early warning signals to determine the most appropriate strategy for each scenario. The implementation plan for each scenario for the next five years was developed based on these strategies.